Force Control of Textile-Based Soft Wearable Robots for Mechanotherapy - (:unkn) unknown (IEEE COMPUTER SOC, 2018)
Soft robotic devices have been utilized in a number of biomedical applications involving human interaction. An emerging opportunity for soft robotic wearable devices is in mechanotherapeutic applications for the recovery and regeneration of soft tissues. Previous studies have implied that judicious force application during mechanotherapy plays an important role in the functional outcome of tissue regeneration. In this paper, we propose soft robotic devices with closed-loop force control to precisely manipulate muscular tissue. The developed devices incorporate fully soft sensors and actuators using textile-based materials and fabrication methods. The closed-loop force control system is demonstrated in bench studies to regulate massage-magnitude forces at frequencies akin to those expected in manual mechanotherapy practices. Testing of the device on human limbs demonstrates the precision and accuracy of the closed-loop force control methodology across different body shapes and types. When commanded to regulate sinusoidal force profiles (with amplitudes of 30N, 45N and 60N), the soft robotic force control device could regulate peak compressive loads to within 0.7N of the desired force. Conversely, open-loop pressure-based control resulted in up to +/-6.6N force tracking variability between participants. A soft robotic system with independently actuatable modules was also fabricated to demonstrate force-controlled actuation patterns to mimic manual massage techniques.
Keywords: RECOVERY; MASSAGE